Conversion of Carbon Monoxide‐Rich Synthesis Gas to Hydrocarbons and Alcohols over Cu/Co/ZnO/SiO2 Catalysts1. Issue 12 (19th October 2015) - Schröder, Johannes; Arnold, Ulrich; Abeln, Johannes; Sauer, Jörg; Döring, Manfred
Abstract: Catalysts of the type Cu/Co/ZnO/SiO2 were prepared by impregnation, subsequent calcination and reduction with hydrogen. Characterization of the catalysts was carried out by ICP‐AES, BET measurements and powder X‐ray diffraction analyses. Furthermore, temperature programmed reduction was employed to investigate their reduction behavior. The catalysts were tested in the conversion of synthesis gas to hydrocarbons and alcohols. High CO conversions could be reached in a single reactor pass. Selectivity was highest for methane, and short‐chain hydrocarbons, but alcohols were also formed. Abstract : In the search for biomass‐based alternatives to fossil fuels, gasification of agricultural wastes shows high potential. Hydrocarbons and alcohols were produced from syngas over Cu/Co/ZnO/SiO2 catalysts. Considerable activity in the conversion of carbon monoxide‐rich synthesis gas was observed and main products were methane and short‐chain alkanes.